Submodeling method to study the residual stress of TBCs near the interfacial asperity on a vane. (April 2021) - Liu, J.H.; Liu, Y.B.; Liu, L.; Yu, Y.H.; He, X.
Highlights: A submodeling method was proposed to simulate the local stress near the interfacial asperity of coatings. Global mechanical analysis of a vane with TBCs was studied. Submodel was established with asperity and divided into three unique zones with proper mesh density according to functions. Submodeling analysis was separately processed but the boundary conditions was prescribed from the results of global analysis. Abstract: Modeling the residual stress of TBCs near the interfacial asperity on turbine component tends to encounter numerical cumbersomeness ordinarily due to huge computational scale and complex mechanical behavior. This paper proposed a numerical method named submodeling method to simulate the local stress near the asperity by a partition model (named submodel) of a coated vane, based on the submodeling technique of ABAQUS code. First a global mechanical analysis about the coated vane was carried lasting three thermal cycles without considering interface asperities. Then a submodel was established with asperity and divided into three unique zones with proper mesh density according to their functions. Finally the local mechanical analysis was separately processed by submodeling method, based on interpolation of the solution from the global analysis onto the outer zone of the submodel. The results show that the stress level of TC near the asperity is relatively low after 3 thermal cycles. The normal stress and the shear stress of BC near the asperity are concentrated in the peak and nearby the trough, respectively. These stress concentrations may lead to TGO/BC interfacial crack. The stress values and distribution feature of BC near the asperity is quite agreement with former results. These may prove that submodeling method can be applicable for local stress modeling and failure prediction.